2004
DOI: 10.1590/s0100-06832004000100009
|View full text |Cite
|
Sign up to set email alerts
|

Densidade e diversidade fenotípica de bactérias diazotróficas endofíticas em solos de mineração de bauxita, em reabilitação

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
26

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 9 publications
(12 reference statements)
0
5
0
26
Order By: Relevance
“…Further studies carried out by her group on the ecology of Azospirillum in heavy metal contaminated area as well as in bauxite mining reclamation area showed that the population of Azospirillum was similar to the one detected in non-contaminated agricultural ecosystems, but was drastically reduced in the bauxite mining area. On the other hand, the use of several gramineous species in this area promoted a qualitative and quantitative increase in diazotrophic bacteria populations with values higher than those observed for reference areas (Melloni et al 2004). The analysis of the nitrogenfixing bacteria present in these areas showed a high diversity of the diazotrophs including Azospirillum and Herbaspirillum species as well as other unidentified ones ).…”
Section: Ecological and Colonization Studiesmentioning
confidence: 63%
“…Further studies carried out by her group on the ecology of Azospirillum in heavy metal contaminated area as well as in bauxite mining reclamation area showed that the population of Azospirillum was similar to the one detected in non-contaminated agricultural ecosystems, but was drastically reduced in the bauxite mining area. On the other hand, the use of several gramineous species in this area promoted a qualitative and quantitative increase in diazotrophic bacteria populations with values higher than those observed for reference areas (Melloni et al 2004). The analysis of the nitrogenfixing bacteria present in these areas showed a high diversity of the diazotrophs including Azospirillum and Herbaspirillum species as well as other unidentified ones ).…”
Section: Ecological and Colonization Studiesmentioning
confidence: 63%
“…Os 72 isolados de bactérias diazotróficas estudados, oriundos de amostras de horizonte superficial de um Cambissolo distrófico, foram coletados de dez áreas da ALCOA Alumínio S/A, localizadas em Poços de Caldas (MG) (Quadro 1), e descritos detalhadamente em Melloni et al (2004). O isolamento destas bactérias foi efetuado no laboratório de Microbiologia do Solo/DCS/UFLA (Melloni et al, 2004), utilizando meios de cultura que favorecem o crescimento de diferentes diazotróficos: JNFb (Herbaspirillum spp.…”
Section: Methodsunclassified
“…O isolamento destas bactérias foi efetuado no laboratório de Microbiologia do Solo/DCS/UFLA (Melloni et al, 2004), utilizando meios de cultura que favorecem o crescimento de diferentes diazotróficos: JNFb (Herbaspirillum spp. ), NFb (Azospirillum spp.)…”
Section: Methodsunclassified
See 2 more Smart Citations